Recognition of shared past sufferings, trust and improving intergroup attitudes in Belgium - Alejandra Alarcón-Henríquez (Revista de Psicología, 2010)
This article examines the role of intergroup trust and recognition of past sufferings on intergroup attitudes. We conducted an experiment among Dutch-speaking students in which we manipulated the degree of importance that French-speakers gave to historical episodes of past victimizations in order to test its impact on the attitudes towards the French-speakers. Results show that intergroup attitudes were most favorable among the high-trusting Dutch-speaking participants when they were led to believe that the French- speakers judged important the events where both communities were considered as victims, compared to the conditions where only French-speaking or only Dutch-speaking sufferings were considered important. This suggests some level of intergroup trust is a condition for the positive effect of shared memories of victimization on attitudes.